First and fast : outpace your competitors, lead your markets, and accelerate growth - Cross, Stuart. (Strategic management collection., 2016)
For the past 30 years, business leaders have been exhorted to move faster and adopt a "ready, fire, aim" approach to the growth of their business. As the level of change and turbulence increases in all markets, all organizations must adapt--quickly!--or risk decline and decay. But what are the real behaviors, processes, and techniques that are critical to lead your organization at pace without creating confusion, frustration, and unnecessary risk? First and Fast provides business leaders with a comprehensive and pragmatic set of tools and ideas to enable them to increase pace, build momentum, and accelerate growth in a systematic way. This book is written for business owners, chief executives, other senior executives and managers, consultants, and business advisors. Readers will benefit by learning techniques to build and lead faster, more responsive organizations that are better able to grow and thrive in a fast-changing world. Among other things, they will know how to ensure that managers don't fall into the trap of sitting on yesterday's success when they should be shifting gears to deliver tomorrow's solutions, to demonstrate the necessary fast-paced leadership behaviors on a daily basis, and to transform their business from a "busy" organization to one that is genuinely the fastest and most effective in its market.